Assessment of thermal change in cold avalanching glaciers in relation to climate warming. Issue 15 (6th August 2015) - Gilbert, A.; Vincent, C.; Gagliardini, O.; Krug, J.; Berthier, E.
Abstract High‐elevation glaciers covered by cold firn are undergoing substantial warming in response to ongoing climate change. This warming is affecting the ice/rock interface temperature, the primary driver of avalanching glacier instability on steep slopes. Prediction of future potential instability therefore requires appropriate modeling of the thermal evolution of these glaciers. Application of a state‐of‐the‐art model to a glacier in the French Alps (Taconnaz) has provided the first evaluation of the temperature evolution of a cold hanging glacier through this century. Our observations and three‐dimensional modeling of the glacier response (velocity, thickness, temperature, density, and water content) to climate change indicate that Taconnaz glacier will become temperate and potentially unstable over a large area by the end of the 21st century. The risk induced by this glacier hazard is high for the populated region below and makes observation and modeling of such glaciers a priority.